The Comparative Study of Spinal Alignment and Trunk Injuries in Freestyle and Greco-Roman Wrestlers - siamak amirian; Bahman Mirzaei; Hossein Hosseini (Sport Sciences and Health Research)
The aim of this study was to compare spinal alignment and trunk injuries in freestyle and Greco-Roman wrestlers. For this purpose, 200 professional wrestlers (100 freestyle and 100 Greco-Roman) were selected randomly. Injury questionnaire was used to collect trunk injury data. Also, 50 freestyle wrestlers and 50 Greco-Roman wrestlers were selected to assess their spinal alignment using spinal mouse. Craniovertebral angle was measured through picturing the side view of head and neck using AutoCAD software. The data were analyzed by t student test. The results indicated that the neck injuries of freestyle wrestlers were significantly higher than Greco-Roman wrestlers (P=0.035), but the rib fracture (P=0.033) and craniovertebral angle (P=0.048) were significantly higher in Greco-roman wrestlers than freestyle wrestlers. There was no significant difference in muscular, articular, back and waist injuries, kyphosis and lordosis between Greco-Roman and freestyle wrestlers (P>0.05). According to the results of this study, freestyle wrestling techniques should be instructed more professionally because one of the main reasons of neck injury is poor performance of underrun technique and other techniques that makes neck to get involved in the opponent's hands. Greco-Roman wrestlers should also be instructed to bend their knees to use quadriceps muscle rather than erector spinae muscle for lifting an opponent.